LANGUAGE AND SPEECH EVALUATION IN STATICS AND DYNAMICS (Academia Science Repository, 2023)
The article is devoted to the consideration of the issues of statics and dynamics in the process of the historical change of the language. There are specific unchanging universal properties that can be found in all languages at all stages of their development: the division of sounds into vowels and consonants, the distinction between the main parts of speech and parts of a sentence, etc. The ratio of stable and variable characteristics varies in different historical periods and at different linguistic levels, but there is practically no doubt that we can find statics and dynamics both in synchronicity and in diachrony.